The “7% solution” and IPO (under)pricing - Busaba, Walid Y.; Restrepo, Felipe (Journal of Financial Economics, 2022)
We investigate the effect of the “7% solution”—the fact that underwriters in the U.S. charge a 7% spread to most IPOs between 20 million and 100 million in size—on the ensuing pricing of the offerings. Our identification exploits the variation in spreads that is due to distinct kinks in the relation between spread and offer size at these two thresholds. We find the spread positively influences underpricing but also the offer-price adjustment from the filing range's midpoint. Our evidence indicates the spread influences the aftermarket price, suggesting underwriters can shape, not merely discover, investor valuations.